The Q-System as a Synthetic Transcriptional Regulator in Plants - Persad, Ramona; Reuter, D. Nikki; Dice, Lezlee T.; Nguyen, Mary-Anne; Rigoulot, Stephen B.; Layton, Jessica S.; Schmid, Manuel J.; Poindexter, Magen R.; Occhialini, Alessandro; Stewart, C. Neal; Lenaghan, Scott C. (Frontiers in Plant Science, 2020)
A primary focus of the rapidly growing field of plant synthetic biology is to develop technologies to precisely regulate gene expression and engineer complex genetic circuits into plant chassis. At present, there are few orthogonal tools available for effectively controlling gene expression in plants, with most researchers instead using a limited set of viral elements or truncated native promoters. A powerful repressible-and engineerable-binary system that has been repurposed in a variety of eukaryotic systems is the Q-system from Neurospora crassa. Here, we demonstrate the functionality of the Q-system in plants through transient expression in soybean (Glycine max) protoplasts and agroinfiltration in Nicotiana benthamiana leaves. Further, using functional variants of the QF transcriptional activator, it was possible to modulate the expression of reporter genes and to fully suppress the system through expression of the QS repressor. As a potential application for plant-based biosensors (phytosensors), we demonstrated the ability of the Q-system to amplify the signal from a weak promoter, enabling remote detection of a fluorescent reporter that was previously undetectable. In addition, we demonstrated that it was possible to coordinate the expression of multiple genes through the expression of a single QF activator. Based on the results from this study, the Q-system represents a powerful orthogonal tool for precise control of gene expression in plants, with envisioned applications in metabolic engineering, phytosensors, and biotic and abiotic stress tolerance.